Use of Transcranial Doppler ultrasound as Confirmatory Test in Brain death - Winitprichagul, Supharat (Journal of Thai Stroke Society, 2021)
A diagnosis of brain death requires a strict clinical diagnosis and methods: an apnea test for the absence of chest and abdominal movements when the respirator has stopped. However, in case where apnea test is not available, an ancillary test may be used to help assess brain cell activity or to determine the absence of blood flow to the brain (cerebral circulatory arrest: CCA) for the diagnosis of brain death. Transcranial Doppler Ultrasound (TCD) can be used to confirm CCA whiles transmits high-frequency waves to detect the flow of blood in the arteries and interprets the changed pattern of Doppler spectral waveform in each phase correlate with intracranial pressure (ICP) increases. The advantages of TCD as a safe tool and there is no risk of using contrast agent. TCD can be done at the bedside and can repeat studies for follow-up. Limited TCD, as the patient’s skull must be intact. And may not be examined in patients with thick temporal skull (poor temporal window), etc. TCD should be examined and interpreted by a well-trained person.